Life cycle of Cosmolaelaps jaboticabalensis (Acari: Mesostigmata: Laelapidae) on Frankliniella occidentalis (Thysanoptera: Thripidae) and two factitious food sources - Moreira, Grazielle Furtado [UNESP]; Morais, Matheus Rovere de [UNESP]; Busoli, Antnio Carlos [UNESP]; Moraes, Gilberto José de (Springer, 2015)
The aim of this work was to study the life cycle of Cosmolaelaps jaboticabalensis Moreira, Klompen and Moraes preying on Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), a serious cosmopolitan pest of different crops, as well as on Protorhabditis sp. (Nematoda: Rhabditidae) and Tyrophagus putrescentiae (Astigmatina: Acaridae), prospective factitious foods for the mass rearing of the predator. Experiments were conducted in a chamber at 25 +/- A 1 A degrees C, 70 +/- A 10 % RH and in the dark. Total immature development (egg-adult) was completed in 12.3 +/- A 5, 6.6 +/- A 0.6 and 7.1 +/- A 0.6 on F. occidentalis, Protorhabditis sp. and T. putrescentiae, respectively. Fecundity and intrinsic rate of increase were higher on Protorhabditis sp. (71.6 +/- A 9.1 eggs/female; 0.28 female/female/day) than on F. occidentalis (63.8 +/- A 14.8; 0.23) and T. putrescentiae (43.1 +/- A 8.9; 0.23). Cosmolaelaps jaboticabalensis reproduces by thelytokous parthenogenesis and its larval stages can be completed without feeding. Protonymphs and deutonymphs can survive in the absence of food for about a month, and adults for almost 2 months. It was concluded that C. jaboticabalensis is a promising biological control agent of F. occidentalis and that it may be mass reared with the use of Protorhabditis sp. or T. putrescentiae.
Keywords: Predatory mites; Biological control; Hypoaspidinae; Life table